5p-p+8+6+3p=4+2p

Simple and best practice solution for 5p-p+8+6+3p=4+2p equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5p-p+8+6+3p=4+2p equation:



5p-p+8+6+3p=4+2p
We move all terms to the left:
5p-p+8+6+3p-(4+2p)=0
We add all the numbers together, and all the variables
5p-p+3p-(2p+4)+8+6=0
We add all the numbers together, and all the variables
7p-(2p+4)+14=0
We get rid of parentheses
7p-2p-4+14=0
We add all the numbers together, and all the variables
5p+10=0
We move all terms containing p to the left, all other terms to the right
5p=-10
p=-10/5
p=-2

See similar equations:

| 3a-2a+a=36 | | Y=5x⁴ | | 17a-16a=16 | | xx3=729 | | (1.31x)+(1.08x)+x=44 | | 2D²+3D+4=x²-2x | | (1.5x)+(1.3x)+x=38 | | 2x*3x=12 | | 35/3x=210 | | 2/5+n=4/5 | | 24=4(-3x+12 | | 7X3(8x+6)=17 | | 3(4.5-2x)-1.8(x+5)=5(1.5-1.4) | | d) 7X2+28X=0 | | 45x+90=540 | | 7.4=n-2.6* | | -5=m+11* | | 15−4√36=x | | b) X2+5X=0 | | F(x)=4x^2-8x+13 | | F(x)=-6×*2+24×-20 | | 57-5x=8x+5 | | (7x−6)=(8x-27) | | 4x-15-10=0 | | 3x−17=–26 | | 0.8(3p+12)=8p | | m-m-1/2=4-m-2/3 | | 6*x*3.5x=2100 | | X+8x-3=42 | | 2x+3/8x-5=3/2 | | 6z+11=89 | | 4x(x+7)=6x+40 |

Equations solver categories